Electricity Networks in a Net-Zero-Carbon Economy - Bassam Fattouh; Farhad Billimoria; Christine Brandstätt; Rahmat Poudineh (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2020)
This issue of Oxford Energy Forum (OEF) is dedicated to electricity networks. Over the last decade, decarbonization, decentralization and digitalization (3D) have transformed the electricity system. Within this changing environment electricity networks are required to remain stable and secure while additionally facilitating net-zero-carbon policies. The increased level of low-carbon heating/cooling and transport along with changes in the operating environment of networks due to 3D trends mean that these companies need to transform to support decarbonization. There may be a need for further investments in grid capacity, but less so if networks have the incentives to support the decentralization paradigm in a way that reduces the costs of network reinforcement. New sources of flexibility – such as distributed generation, storage, and demand response – provide alternative solutions to both short-term congestion management and long-term capacity upgrades. From a system perspective, however, minimizing the network costs – and consequently the cost of achieving decarbonization targets – requires a higher level of strategic coordination than the current energy governance delivers. This coordination needs to occur not just between transmission and distribution networks but also between electricity and gas and other energy vectors such as heat and hydrogen. . Therefore, it is important to reassess, adjust and innovate regulation, market design as well as roles and institutions to enable electricity networks to make efficient investment and operational decisions and integrate an increasing breadth of network users.
Keywords: 330